EFEKTIVITAS PENGGUNAAN KARTU KUARTET PADA PENGUASAAN BAHASA ARAB - Fazri Nur Insan Tamami; Nurhidayati; Muhammad Ruzalul Furqon (Tarling : Journal of Language Education, 2025)
The purpose of this study is to explore the effectiveness of using quartet card media in improving students’ mastery of Arabic vocabulary. This research adopts a pre-experimental approach with a one-group pre-test and post-test design. The data collected comprise both qualitative and quantitative types. Qualitative data were obtained through documentation and relevant literature reviews, while quantitative data were gathered through test results conducted before and after the implementation of the media. The data were analyzed using SPSS version 23. The findings revealed that the student’s average score in Arabic vocabulary before using of the quartet card media was 84, which increased significantly to 99 after the treatment. Moreover, the N-Gain Percent calculation showed a result of 87.5%, which is categorized as high. This indicates that the use of quartet cards as a learning medium is effective in enhancing students’ vocabulary acquisition. Therefore, quartet card media can be considered a valuable tool in Arabic language learning, especially for vocabulary development.